Impacts of climate change on crop and irrigation water requirement in the Savannah regions of Ghana - Incoom, A. B. M.; Adjei, K. A.; Odai, S. N.; Akpoti, Komlavi; Siabi, E. K. (IWA Publishing, 2022)
Water sources remain the key sources of irrigation in semi-arid regions. However, future climate changes threaten these sources. The study analysed water requirements of two commonly cultivated crops in the dry season in the Ghanaian Savannah regions under baseline and future periods. Crop water requirement (CWR) and crop irrigation requirement (CIR) were lowest in baseline periods and increased in the 2020 s, 2050 s, and 2080 s for RCP 4.5 and RCP 8.5 at all locations. CIR was higher for tomato as compared to onions for most locations. Seasonal changes in the CWR ranged from 2–9, 3–12, and 3–12% and 2–8 3–12% and 5–18% for the 2020 s, 2050 s and 2080 s under RCP 4.5 and RCP 8.5, respectively, for both the crops. Bole and Zuarungu recorded highest increases in CWR for tomato, whereas the least change was observed at Yendi for onions. Changes in seasonal CIR ranged from 3–19, 2–21, and 6–22%, respectively, for the 2020 s, 2050 s and 2080 s for RCP 4.5. Under RCP 8.5, changes in seasonal CIR ranged from 3–23, 5–23, and 6–27% were observed for the 2020 s, 2050 s, and 2080 s, respectively. Highest increases in CIR were noticed at Bole and Zuarungu for tomato, whereas the least change was observed at Wenchi for onions. Findings of the study support zero hunger and climate action, goals 2 and 13 of the SDGs.